Direction dependence of displacement time for two-fluid electroosmotic flow - Lim, Chun Yee (2013)
Electroosmotic flow that involves one fluid displacing another fluid is commonly encountered in various microfludic applications and experiments, for example, current monitoring technique to determine zeta potential of microchannel. There is experimentally observed anomaly in such flow, namely, the displacement time is flow direction dependent, i.e., it depends if it is a high concentration fluid displacing a low concentration fluid, or vice versa. Thus, this investigation focuses on the displacement flow of two fluids with various concentration differences. The displacement time was determined experimentally with current monitoring method. It is concluded that the time required for a high concentration solution to displace a low concentration solution is smaller than the time required for a low concentration solution to displace a high concentration solution. The percentage displacement time difference increases with increasing concentration difference and independent of the length or width of the channel and the voltage applied. Hitherto, no theoretical analysis or numerical simulation has been conducted to explain this phenomenon. A numerical model based on finite element method was developed to explain the experimental observations. Simulations showed that the velocity profile and ion distribution deviate significantly from a single fluid electroosmotic flow. The distortion of ion distribution near the electrical double layer is responsible for the displacement time difference for the two different flow directions. The trends obtained from simulations agree with the experimental findings.